Determination of fat and moisture in olives by nearinfrarred reflectance spectroscopy - A. Jiménez; E. Izquierdo; F. Rodríguez; J. I. Dueñas; C. Tortosa (Grasas y Aceites, 2000)
A near-infrarred reflectance (NIR) equipment with optical based on interference filters was used. Lineal combination of these filters were obtained for measuring oil content and moisture in olives. A good correlation in the interval 15.70% to 33.00%, between olive oil content predicted by near-infrarred and data obtained with the Soxhlet method has been obtained (correlation coefficient r=0.9908 and estandar error of prediction SEP=0.811). For moisture, a good correlation, in the interval 36.5%-65.0% between measures obtained by near-infrarred prediction and the reference dry-oven method was also observed (r=0.9939 and SEP=0.928). With a near-infrarred technique measurement of both parameter can be takes concurrently and in a few seconds. Chemical reagents and complex sample preparation are not required, only milling of drupes by a hammer crusher.